Peculiarities of Post Cryopreservation Changes in Structural and Functional Characteristics of Hematopoietic Stem Cells Derived from Various Source - Goltsev, Anatoly N.; Dubrava, Tatiana G.; Gaevskaya, Yulia A.; Yampolskaya, Ekaterina E.; Ostankova, Lyudmila V.; Ostankov, Maksim V. (Problems of Cryobiology and Cryomedicine, 2014)
The performed comparative analysis of structural and functional status of fetal liver (FL) hematopoietic stem cells (HSCs) of 14 gestation days and adult bone marrow (BM) of 4-month-old CBA/H mice demonstrated not only the differences of their initial qualitative and quantitative characteristics but also different responses to the effect of cryopreservation factors. Either FL or BM cells were frozen according to various regimens under protection of 5 and 10% dimethyl sulfoxide. To estimate structural and functional characteristics of HSCs derived from different sources there were used cytofluorimetry (content of CD34+СD38– cells), methods of colony formation in vivo (CFUs) and in vitro (CFU-GM). It has been established that certain cryopreservation regimens are able to manifest the effect of selective enrichment of cell populations with phenotype of hemopoietic progenitors (CD34+CD38– cells). Comparing the content of CFUs, CFU-GM, HSCs and cells with CD34+CD38– phenotype has shown that cryopreservation regimen for FL cells was not optimal for BM. It has been demonstrated that varying cryopreservation conditions allowed not only to provide optimal preservation rate of hemopoietic progenitors derived from FL and BM with various initial functional status, but to control it purposefully. Probl Cryobiol Cryomed 2014; 24(2):118-131.